Innovation Strategy Based on Shiwam Satyam Sundharam to Increase Competitive Advantage in Wood Crafts in Gianyar Regency - Arsha, I Made Risma M; Mahayasa, I Gede Aryana; Puja, I Made Suasti (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Balinese handicraft products are synonymous with soul and art based on local wisdom values that become local knowledge and local skills as a form of originality that is not owned by other regions so that it will be easier for companies to achieve sustainable competitive advantage (Ife, 2002; Mardatillah et al., 2020). Wood handicraft SMEs in Bali Province are known to have a high artistic spirit, creativity and innovation and have their own characteristics or uniqueness. The artistic spirit is passed down from generation to generation and is an integral part of the daily activities of the craftsmen. This research uses quantitative research methods, which are based on the positivism paradigm. The analysis continued at the quantitative analysis stage based on multivariate analysis using structural equation modeling (SEM) based on Partial Least Square (PLS). Problems in the competitive advantage of wood handicraft SMIs in Bali can be seen from their low production value when compared to other existing industries. Bali as a craft center is certainly a large market for consumers both at home and abroad. This of course makes wood handicraft SMIs require a competitive advantage that can be highlighted and become a differentiator with other similar industrial products. This research was conducted on wood handicraft SMIs in Gianyar Regency. This is done because Gianyar is famous for its many wood craftsmen who have a high artistic spirit and creativity. The population of this study was all wood handicraft SMIs in Gianyar Regency which amounted to 476 businesses.